Morphophonological patterns influence regular and irregular past-tense production: evidence from aphasia. Issue 3 (16th March 2023) - Rimikis, Stacey; Buchwald, Adam; Miozzo, Michele
ABSTRACT: Previous work has demonstrated that the distribution of morphophonological patterns in the lexicon influences how unimpaired speakers inflect novel nonwords (Albright & Hayes [2003]. Rules vs. Analogy in English past tenses: A computational/experimental study. Cognition, 90 (2), 119–161). Here, we investigated whether morphophonological patterns impact the language production of a group of individuals with acquired language impairment ( n  = 16). Using a past-tense production task, we found that both accuracy and error patterns were impacted by the distribution of morphophonological patterns. Participants were more accurate producing regular verbs when more phonologically similar verbs also take the regularised past tense form. Additionally, regularisation errors for irregular verbs (e.g. runned ) occurred more frequently when the regularised form occurred more in phonologically similar verbs. These effects occurred across and within allomorphic subgroups of the regular past tense (i.e. stem+/t/, stem+/d/, stem+/əd/). Taken together, these results indicate that speakers are sensitive to the distribution of morphophonological patterns in the language at a high degree of granularity .